Modulating microenvironments to enhance CO2 electroreduction performance - Dan Wang; Junjun Mao; Chenchen Zhang; Jiawei Zhang; Junshan Li; Ying Zhang; Yongfa Zhu (eScience, 2023)
Microenvironments of the catalytic center, which play a vital role in adjusting electrocatalytic CO2 reduction reaction (ECO2RR) activity, have received increasing attention during the past few years. However, controllable microenvironment construction and the effects of multi-microenvironment variations for improving ECO2RR performance remain unclear. Herein, we summarize the representative strategies for tuning the catalyst and local microenvironments to enhance ECO2RR selectivity and activity. The multifactor synergetic effects of microenvironment regulation for enhancing CO2 accessibility, stabilizing key intermediates, and improving the performance of ECO2RR catalysts are discussed in detail, as well as perspectives on the challenges when investigating ECO2RR microenvironments. We anticipate that the discussions in this review will inspire further research in microenvironment engineering to accelerate the development of the ECO2RR for practical application.